Factors Influencing Students’ Application And Enrolment Decisions In Higher Education: A Perception-Based Empirical Study With Reference To Uttar Pradesh, India - Dr Hari Mohan Saxena, Mrs. Mohini Gupta, Dr Sameer Kumar (European Economic Letters (EEL), 2025)
This study examines the complex variables influencing students' admission decisions to tertiary institutions. In a more competitive and diversified academic environment, it is important to identify the determinants of students' choices for institutions that want to attract appropriate candidates and for policymakers who want to promote, access and equity. The study uses a [state methodology, i.e., mixed-methods approach, quantitative survey, qualitative interviews] in order to analyze the relative impact of academic factor, financial factors, career related factors, place and campus environment and personal & social factors on the application and enrollment decisions of the students. Data is gathered from undergraduate students, of Uttar Pradesh. The results are anticipated to gain insight into the intricate dynamics of personal aspirations, socio-economic conditions, and institutional properties underpinning student decisions in higher education and feeding back into informing institutional strategies and policy interventions for informed and equitable access to tertiary education.